STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN YANATA AC SURABAYA - Herdiyansyah Ramadhany; Diah Ayu Sanggarwati; Iwang Suwangsih (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
In the midst of intense industry competition, Yanata AC Surabaya recognizes the critical importance of enhancing employee performance for achieving success. This research investigates how Management Performance Strategy (MSK) contributes to enhancing the performance of Yanata AC Surabaya's employees. A qualitative approach with qualitative data analysis was employed to uncover the implemented strategies. Data were gathered through observations, interviews, and pertinent documents. The findings indicate that MSK plays a pivotal role in improving employee performance, with the application of discipline and motivational strategies identified as key factors. Specifically, training, enforcement of time management policies, and provision of incentives (both rewards and penalties) are among the strategies implemented. The effectiveness of these approaches is evaluated based on their adherence to MSK principles, including planning, implementation, and evaluation. This study demonstrates that appropriate MSK strategies, such as training, time management enforcement, and incentives, can effectively and efficiently enhance employee performance.